Single versus tandem high-dose melphalan followed by autologous blood stem cell transplantation in multiple myeloma: long-term results from the phase III GMMG-HD2 trial - Mai, Elias K.; Bertsch, Uta; Egerer, Gerlinde; Ho, Anthony Dick; Hillengaß, Jens; Raab, Marc-Steffen; Goldschmidt, Hartmut (British journal of haematology, 2016)
The prospective, randomized phase III trial GMMG-HD2 aimed at demonstrating non-inferiority of single (Arm A) versus tandem (Arm B) high-dose melphalan followed by autologous transplantation (HDM/ASCT) with regard to 2-year event-free survival (EFS) in newly-diagnosed multiple myeloma (MM) and included 358 evaluable patients [Intention-to-treat population, (ITT), single/tandem HDM/ASCT: n = 177/181]. After a median follow-up of more than 11 years, non-inferiority of single versus tandem HDM/ASCT was demonstrated using the planned non-inferiority threshold of 15% of the 2-year EFS rate. Neither EFS (P = 0·53) nor overall survival (OS) (P = 0·33) differences were observed in the ITT population. In the tandem arm, 26% (n = 47/181) of patients refused a second HDM/ASCT due to non-medical reasons. A per-protocol (PP) analysis, including patients who received the intervention (single/tandem HDM/ASCT: n = 156/93) and patients who did not receive a second HDM/ASCT due to medical reasons (12%, n = 22/181), did not yield differences in EFS (P = 0·61) or OS (P = 0·16). In the ITT and PP set of the tandem arm, the rates of complete responses increased from first to second HDM/ASCT (both P = 0·04). Ten-year OS for the entire ITT was 34% (95% confidence interval: 29-40%). OS after first relapse was significantly shortened in the tandem arm (P = 0·04). In this study single HDM/ASCT was non-inferior to tandem HDM/ASCT in MM.
Gesehen am 14.08.2019